Systematic statistical approaches in classifying physical properties of soft marine clay / Lim Jit Kheng … [et al.] - Lim Jit Kheng (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2010)
In this paper, a rational framework in classifying soil properties using systematic statistical approaches has been proposed and illustrated through a case study using some simple physical index properties of soft marine clay in Peninsular Malaysia. The framework includes an initial data screening, followed by trend analysis, removal of outliers, normality conformance and lastly the descriptive statistics. Common erroneous treatments that used to be overlooked were examined in detail and the results of analyses were interpreted statistically incorporating engineering judgment. The effectiveness of various common statistical methods were compared, contrasted and discussed. The proposed framework was found useful in characterizing soil properties and the important findings were listed.